Optimization of natural red colorant production from Roselle using ultrasound-assisted extraction - Mokhtar, N.; Pak Dek, Mohd Sabri; Hamid, A. A.; Mohd Johar, A. H. H.; Jaafar, A. H. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
Roselle (Hibiscus sabdariffa L.) contains high level of anthocyanin and it gains a great consideration as natural red food colorant. Previous study showed several extraction methods have been used to extract natural colorant from plant but no study on the extraction of colorant from Roselle using ultrasound-assisted extraction (UAE) has been reported. Similarly, the information on the stability of Roselle red colorant at different temperature and storage materials is not available in the literature. Therefore, a study aims to optimize UAE conditions for producing red colorant from Roselle. The stability of Roselle red colorant at different temperature and packaging materials was evaluated. UAE optimization started with single factor experiments followed by response surface methodology (RSM). The studied UAE variables for RSM were percentage of sample weight (10-20%), sonication time (10-30 minutes) and pre-incubation time (0-30 minutes). Results of the study showed an optimum UEA condition to extract highest red colorant from Roselle was at 15% sample weight, 10 minutes sonication time and 20 minutes pre-incubation time. The experimental values for these responses were not significantly different with predicted values. Further analysis on the stability of red Roselle colorant at chilled and room temperature using different storage materials namely opaque bottle and clear bottle showed the Roselle red colorant was stable at chilled temperature for both packaging materials. In conclusion, the study showed that UAE can be used to produce red colorant from Roselle and the storage at low temperature is recommended for longer shelf life. This information provides another natural red colorant that can be incorporated in food.